Peripheral Facial Palsy and Communicating Hydrocephalus as a Clinical Presentation of Hemorrhagic Vestibular Schwannoma: Case Report - Silva, João Monteiro; Gomes, Mário; Carvalho, Ernesto de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
The vestibular schwannoma is the most common extra-axial tumor of the posterior fossa. Hemorrhage associated with vestibular schwannomas has been described in less than 1% of the cases. The etiology remains unknown; however, some risk factors have been suggested, such as tumor size and tumor growth rate, the vascularity and histopathology of the tumor or even previous treatment with radiosurgery. The present case is of a 74-year-old female patient, who presented to our clinic in December of 2015 after a mild traumatic brain injury. In that context, she did a brain computed tomography (CT) scan and was diagnosed with a vestibular schwannoma— an incidentaloma. It was decided at that time to treat the patient conservatively because of her comorbidities and the presentation of the disease. In March of 2017, the patient presented again to our clinic with a right peripheral facial paralysis (House-Brackmann [HB] grade IV-VI) and confusion. The CT scan revealed that bleeding around the vestibular schwannoma had caused the clinical presentation. We decided to treat the hydrocephalus with a ventriculoperitoneal shunt. At the time of her last follow-up visit, the confusion symptoms had resolved, and her right-sided facial function had improved to a HB grade II-VI.
Keywords: vestibular schwannoma; brain hemorrhage; hydrocephalus; peripheral facial paralysis